2000
DOI: 10.1038/sj.cdd.4400655
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural localization of cytochrome c in apoptosis demonstrates mitochondrial heterogeneity

Abstract: Release of apoptogenic factors into the cytosol including cytochrome c is triggering the execution phase of apoptosis through activation of cytoplasmic effector caspases. How loss of function of the electron transport chain can be reconciled with an adequate energy supply necessary for executing the apoptotic program was studied in granulosa cell (GC) sheets cultured up to 72 h without gonadotrophic support. Cytochrome c was localized ultrastructurally by oxidation of diaminobenzidine tetrahydrochloride both i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 41 publications
5
32
0
1
Order By: Relevance
“…13 We report that an increase in mitochondrial heterogeneity coincides with the progression of RRECs through apoptosis. In other systems, it has been reported that increased mitochondrial heterogeneity may reflect permeability transition pore opening and the release of cytochrome c. 32,33 Our findings coincide with recent studies of mitochondria biology that have focused on the role of mitochondrial morphology as a regulator of mitochondrial functioning. Most mammalian cell types have long, tubular networks of mitochondria, which is critical to normal mitochondria functioning.…”
Section: Discussionsupporting
confidence: 79%
“…13 We report that an increase in mitochondrial heterogeneity coincides with the progression of RRECs through apoptosis. In other systems, it has been reported that increased mitochondrial heterogeneity may reflect permeability transition pore opening and the release of cytochrome c. 32,33 Our findings coincide with recent studies of mitochondria biology that have focused on the role of mitochondrial morphology as a regulator of mitochondrial functioning. Most mammalian cell types have long, tubular networks of mitochondria, which is critical to normal mitochondria functioning.…”
Section: Discussionsupporting
confidence: 79%
“…Importantly, some of the proteins identified here as enriched among apoptotic vesicles (for example, the actin-associated proteins cofilin and Arp2/3 (37), numerous heat shock proteins, and other chaperones associated with stress (38 -40)) fulfill expectations derived from other studies. Similarly, the mitochondrial protein cytochrome c is known to be released from mitochondria during apoptotic cell death (41,42). It is significant that not all of the vesicle-enriched molecules are membrane-exposed; in particular, we did not detect surfaceexposed cytochrome c (data not shown).…”
Section: Proteomic Analyses Of Apoptotic Membrane Vesicles Reveal Memmentioning
confidence: 61%
“…It is known that a large fraction of cyt-c does not participate in electron transport (27) and hence that cyt-c is present in excess in the mitochondrial intermembrane space. Electron microscopy studies have indicated that the release of cyt-c during apoptosis is a complete process, leading to a total depletion of cyt-c in affected mitochondria (28). There is also evidence that cyt-c is released specifically out of apoptotic cells prior to a loss of plasma membrane integrity (18,29).…”
Section: Discussionmentioning
confidence: 98%